Kesehatan Mental Belajar Terhadap Pencegahan Bullying - Sartika, Andry; Lussyefrida Yanti; Noveriyanto (Gayaku Publisher, 2023)
Bullying is the act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels depressed, traumatized and helpless. Teenagers who are victims of bullying are more at risk of experiencing various health problems, both physically and mentally. The problems that are more likely to be suffered by children who are victims of bullying include the emergence of various mental problems such as depression, anxiety and sleep problems which may be carried over into adulthood, physical health complaints, such as headaches, stomach aches and muscle tension, feeling unwell. safe when in the school environment, and decreased enthusiasm for learning and academic achievement. In quite rare cases, children who are victims of bullying may show violent traits. As experienced by a 15 year old teenager in Denpasar, Bali, who had the heart to kill his own friend because he had a grudge against the victim. The perpetrator admitted that he had often been the target of bullying since the first grade of junior high school. With the education provided to teenagers and health education, it is hoped that children will maintain their attitudes and respect each other between friends and think about the fatal consequences that will occur in the future for victims of bullying, so that they can prevent an increase in bullying cases. This article aims to determine the factors that cause bullying by teenagers, the roles in bullying, and the types of bullying. The data source for this paper was carried out using the documentation study method. In this article, the results show that the factors that influence bullying can come from individuals, families, play groups, and the perpetrator's community environment. This action is closely related to the world of social work, which in this case is required to become a counselor for bullies.